2011
DOI: 10.1021/ac201778h
|View full text |Cite
|
Sign up to set email alerts
|

Hearing What You Cannot See and Visualizing What You Hear: Interpreting Quartz Crystal Microbalance Data from Solvated Interfaces

Abstract: Over the last 2 decades, the quartz crystal microbalance (QCM or QCM-D) has emerged as a versatile tool for investigating soft and solvated interfaces between solid surfaces and bulk liquids because it can provide a wealth of information about key structural and functional parameters of these interfaces. In this Feature, we offer QCM users a set of guidelines for interpretation and quantitative analysis of QCM data based on a synthesis of well-established concepts rooted in rheological research of the last cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
1,079
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 742 publications
(1,109 citation statements)
references
References 79 publications
28
1,079
1
1
Order By: Relevance
“…Adsorption of a certain amount of mass onto the sensor surface leads to a decrease in the frequency of the resonance overtones, 25 although it is not straightforward to establish the correct relationship between both quantities when dealing with viscoelastic materials. 26 Additionally, the coupled mass sensed in QCM-D experiments includes that of the adsorbed film and that of the coupled solvent. 27,28 Thus, it is often referred as "wet mass".…”
Section: Quartz Crystal Microbalance With Dissipation (Qcm-d)mentioning
confidence: 99%
“…Adsorption of a certain amount of mass onto the sensor surface leads to a decrease in the frequency of the resonance overtones, 25 although it is not straightforward to establish the correct relationship between both quantities when dealing with viscoelastic materials. 26 Additionally, the coupled mass sensed in QCM-D experiments includes that of the adsorbed film and that of the coupled solvent. 27,28 Thus, it is often referred as "wet mass".…”
Section: Quartz Crystal Microbalance With Dissipation (Qcm-d)mentioning
confidence: 99%
“…Here, we present and validate a new method for measuring the deformation of nm-sized liposomes adsorbing on surfaces. Although it is based on deducing the height of surface-adsorbed liposomes (labeled as h in Figure 1) from QCM [17][18][19][20][21] measurements, it does not rely on a model. Previously, we showed that this method reliably and quantitatively yields the size of the adsorbed particles for stiff particles that do not deform upon adsorption; in that case, h ∌ 2R (Figure 1(a)), where R is the radius of particles in solution (e.g., measured with dynamic light scattering).…”
Section: Introductionmentioning
confidence: 99%
“…The principle of QCM-D is based on the shift of an electroacoustic resonance frequency (Δf ) by loading of mass. The change in the resonant frequency of the oscillating crystal is proportional to the adsorbed mass on the surface, according to the Sauerbrey equation (1) [16], as long as energy dissipation ΔD/Δf < 4 × 10 −7 Hz −1 for a 5 MHz crystal [17],…”
Section: Methodsmentioning
confidence: 99%